1993
DOI: 10.1364/josaa.10.001818
|View full text |Cite
|
Sign up to set email alerts
|

Application of the spatiochromatic visual evoked potential to detection of congenital and acquired color-vision deficiencies

Abstract: Visual evoked potentials were recorded in response to spatiochromatic stimuli modulated in different directions in cone-activation color space from subjects with congenital and acquired color defects. This technique was effective for detection and classification of both mild and severe forms of congenital deficits. Results suggest that the visual evoked potential is useful for early identification of color abnormalities in acquired deficits such as diabetes and that it is sensitive enough to detect regional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 15 publications
7
48
1
Order By: Relevance
“…The present results are in agreement with previous published literature showing that it is possible to isolate chromatic components of the cortical response by using isoluminant gratings and the appropriate procedures to maximize chromatic response and minimize achromatic intrusion~Carden et al, 1985;Murray et al, 1987;Berninger et al, 1989;Crognale et al, 1993;Rabin et al, 1994;Kulikowski et al, 1997;Porciatti & Sartucci, 1999;Suttle & Harding, 1999;Gomes et al, 2006 Tobimatsu et al, 1995;Porciatti & Sartucci, 1999;Gomes et al, 2006! demonstrated that it is possible to evaluate color discrimination thresholds both in dichromats and normal trichromats by using transient VEP and measuring the N1 peakto-baseline amplitude, and that this procedure shows a good correlation with psychophysical measurements.…”
Section: Transient Onset/offset Vepssupporting
confidence: 93%
“…The present results are in agreement with previous published literature showing that it is possible to isolate chromatic components of the cortical response by using isoluminant gratings and the appropriate procedures to maximize chromatic response and minimize achromatic intrusion~Carden et al, 1985;Murray et al, 1987;Berninger et al, 1989;Crognale et al, 1993;Rabin et al, 1994;Kulikowski et al, 1997;Porciatti & Sartucci, 1999;Suttle & Harding, 1999;Gomes et al, 2006 Tobimatsu et al, 1995;Porciatti & Sartucci, 1999;Gomes et al, 2006! demonstrated that it is possible to evaluate color discrimination thresholds both in dichromats and normal trichromats by using transient VEP and measuring the N1 peakto-baseline amplitude, and that this procedure shows a good correlation with psychophysical measurements.…”
Section: Transient Onset/offset Vepssupporting
confidence: 93%
“…cVEP provides a noninvasive, sensitive and objective measure of chromatic input in visual pathways. 14 Participants are directed to stare at the stimuli that alternate between 'on' (100 ms) and 'off' (400 ms) while brain waves are measured in the occipital cortex. cVEP is suitable for individuals with ADHD, since it is a purely perceptual task in which the stimuli are presented very briefly, and does not require executive function, sustained or selective attention, or motoric response.…”
Section: Introductionmentioning
confidence: 99%
“…Crognale et al applied chromatic visual evoked potentials in numerous clinical settings and demonstrated specific alterations in, for instance, congenital and acquired colour deficiencies [5], central serous choroidopathy, optic neuritis, and multiple sclerosis [6,7].…”
Section: Introductionmentioning
confidence: 99%